Evaluating the effect of the number of generations in IBUN 91.2.98 Leuconostoc mesenteroides cultures on enzyme extract production - Gustavo Buitrago Hurtado (Ingeniería e Investigación, 2013)
This work studied the effect of the number of generations of the IBUN 91.2.98 Leuconostoc mesenteroides strain on enzyme complex production. The subculturing technique was used on a medium which had been designed specifically for this organism for producing an enzyme complex. The effect was indirectly determined by monitoring microorganism growth and measuring the glucosyltransferase and hydrolytic activity of an enzyme extract obtained from such culture. There were 40 subcultures, representing 196 generations of IBUN 91.2.98 Leuconostoc mesenteroides. The results led to establishing that the extract’s higher enzymatic activity (from 4 to 6 U/mL) was reached at the end of the culture’s exponential phase and that this activity was stable during subculturing, confirming that there was no variation in strain regarding enzyme extract production until such number of generations had occurred, thereby not being limited to scaling-up to 8,000 litres.